2004
DOI: 10.1093/brain/awh333
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of magnetoencephalography results to obtain favourable outcomes in epilepsy surgery

Abstract: Magnetoencephalography (MEG) is a well-known technique in the presurgical evaluation of epilepsy patients. Like EEG, it can detect and localize epileptic activity. Epilepsy surgery can be used to evaluate MEG source localizations. Resection volumes were determined in 33 epilepsy surgery patients. The resection volume, taken together with the post-operative outcome, was used to evaluate MEG results. The scattering MEG localizations of interictal epileptic activity were represented by an ellipsoidal volume. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(100 citation statements)
references
References 14 publications
6
90
0
2
Order By: Relevance
“…Some used anatomical measures such as SECDs located contiguously within neighbouring gyri (Oishi et al, 2006). Others used an ellipsoid model to display results from hierarchical cluster analysis (Fischer et al, 2005). The lack of a consistent and clinically relevant definition of cluster characteristics may also account for discrepancies in the literature that reviews the effect of resection in the presence of MEG clusters: some authors report better results when a single cluster was removed in its entirety (Fischer et al, 2005;Oishi et al, 2006;Vadera et al, 2013), whereas others did not find a clear correlation between the proportion of dipoles within the resection volume with the probability of subsequent seizure-freedom (Kim et al, 2013).…”
Section: Meg Cluster Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some used anatomical measures such as SECDs located contiguously within neighbouring gyri (Oishi et al, 2006). Others used an ellipsoid model to display results from hierarchical cluster analysis (Fischer et al, 2005). The lack of a consistent and clinically relevant definition of cluster characteristics may also account for discrepancies in the literature that reviews the effect of resection in the presence of MEG clusters: some authors report better results when a single cluster was removed in its entirety (Fischer et al, 2005;Oishi et al, 2006;Vadera et al, 2013), whereas others did not find a clear correlation between the proportion of dipoles within the resection volume with the probability of subsequent seizure-freedom (Kim et al, 2013).…”
Section: Meg Cluster Characteristicsmentioning
confidence: 99%
“…Others used an ellipsoid model to display results from hierarchical cluster analysis (Fischer et al, 2005). The lack of a consistent and clinically relevant definition of cluster characteristics may also account for discrepancies in the literature that reviews the effect of resection in the presence of MEG clusters: some authors report better results when a single cluster was removed in its entirety (Fischer et al, 2005;Oishi et al, 2006;Vadera et al, 2013), whereas others did not find a clear correlation between the proportion of dipoles within the resection volume with the probability of subsequent seizure-freedom (Kim et al, 2013). In addition to the lack of consensus regarding definition of cluster, one needs to be reminded that the density, distribution, and extent of MEG dipoles do not just reflect the size of the epileptogenic generator, but are also determined by the type of spikegenerating pathology as well as the signal to noise ratio of the recording (Bagic et al, 2011).…”
Section: Meg Cluster Characteristicsmentioning
confidence: 99%
“…For each subject, the center of mass of the fitted ECDs was first calculated as the mean of all ECD coordinates across all sEMG channels, for each HD-sEMG derivation separately. Then, to characterize the spread of the ECDs, their coordinates relative to their center of mass were subjected to a principal component analysis to construct an ellipsoid centered on their center of mass, with the lengths of the axes along principal components equal to one standard deviation as derived from singular values (Fischer et al 2005). The volume and major axis of this ellipsoid provided a measure of the degree of the ECD spread around the center of mass.…”
Section: Data Processingmentioning
confidence: 99%
“…24 In addition, previous reports have demonstrated more favorable seizure outcomes when the resection area includes the MEG spike cluster. 4,21 A recent study from another institution demonstrated similar results for patients with extratemporal epilepsy. That series included 31 patients who did not undergo invasive monitoring, including several with temporal lobe epilepsy.…”
Section: Discussionmentioning
confidence: 67%